The wizard of lies [videorecording (DVD)] - De Niro, Robert; Pfeiffer, Michelle, 1957-; Nivola, Alessandro; Henriques, Diana B. (Home Box Office, 2017)
It is the headline-making true story about the deceptions, lies and betrayals of Bernie Madoff, the man who masterminded the most heinous financial swindle of our generation.